Dinâmica de colisões eletrônicas com moléculas orgânicas voláteis: seções de choque de ionização e diferenciais elásticas - Silva, Luis Augusto da (2016)
ELECTRONIC COLLISIONS WITH VOLATILE ORGANIC MOLECULES: IONIZATION AND ELASTIC DIFFERENTIAL CROSS SECTIONS. In this work we report an experimental investigation of the dissociative ionization processes induced by electron impact in tetrahydrofuran molecules (THF). Specifically, total ionization cross sections (TICS) and partial ionization cross sections (PICS) were determined in the 10 to 800 eV energy range. Also, same energy range differential cross sections (DCS) were measured for the elastic scattering of electrons for various volatile organic species: acetone, methyl formate, ethyl acetate, acetaldehyde and dimethyl disulfide. The experiments were performed using a Time-Of-Flight (TOF) mass spectrometer and an electron scattering spectrometer, both developed at the Laboratory of Electronic and Photonic Collisions (LCEF) of the Department of Chemistry at UFSCar, São Carlos, Brazil. The absolute values of the cross sections were obtained by the relative flow technique (RFT). Except for the TICS of THF molecule, there are not previous data reported in the literature for comparison with our results. The present experimental data were compared with results obtained in the theoretical frame of the Binary EncounterBethe (BEB), calculations performed in the frame of the independent atoms model (IAM) and other calculated results available in the literature. Compared with BEB results our experimental TICS are systematically higher, but in good agreement with other previous experimental data available. Our DCS experimental data, in general show good agreement with the theoreticals results.